Metabolic syndrome is a key determinant of coronary microvascular function in patients with stable coronary disease and optimal low-density lipoprotein cholesterol levels undergoing percutaneous coronary intervention. (22nd September 2015) - Melikian, N; Shah, A; Byrne, J; Thomas, M; Sherwood, R; Dworakowsk, R; Kearney, M; MacCarthy, P
Abstract : Objective: To examine the influence of the metabolic syndrome (MS; defined by ATP-III criteria) on coronary microvascular function (CMF) in patients on optimal therapy with statins undergoing percutaenous coronary intervention (PCI). Background: CMF determines cardiovascular prognosis. However, there are limited data on the influence of the MS, a major risk factor for vascular disease, on CMF. Methods and Results: 54 patients with stable coronary disease undergoing PCI were divided into two groups according to the presence/absence of MS (mean age (years), MS (n  =  20): 61 ± 11; no MS (n  =  34): 66 ± 8, p = 0.10). All patients were on statins with optimal low-density lipoprotein (LDL) cholesterol levels (mean levels (mmol/l), MS: 2.0 ± 1.0; no MS: 2.1 ± 0.6, p = 0.79). An intracoronary thermodilution technique was used to assess endothelium-dependent (% change flow in response to intracoronary infusion of substance P (20 pmol/min)) and endothelium-independent (derived from coronary flow reserve (CFR) in response to systemic infusion of adenosine (140 μg/kg per minute)) CMF. Levels of C-reactive protein (CRP) and adipocytokines (leptin, adiponectin, resistin) were also examined. Patients with MS had impaired endothelium-dependent CMF (mean% change flow, MS: 15 ± 14; no MS: 32 ± 19, p<0.001). There was no difference in endothelium-independent CMF (CFR, MS: 3.0 ± 1.2; no MS: 3.4 ± 1.8, p = 0.31). Levels of CRP (p = 0.79), leptin (p = 0.48), adiponectin (p = 0.64) and resistin (p = 0.39) were also similar between the two groups. The association between diagnostic ATP-III criteria for MS and CMF was examined. Systolic (r  =  −0.51, p<0.01) and diastolic (r  =  −0.47, p<0.01) blood pressure were the only correlates of endothelium-dependent CMF. In addition, one way analysis of variance showed a linear negative trend between endothelium-dependent CMF and the number of ATP-III diagnostic features in each subject (F  =  4.63, p<0.01). There was a similar trend after the removal of blood pressure as a variable (F  =  3.21, p = 0.04) confirming that non-blood pressure ATP-III diagnostic ATP-III criteria also influence CMF. There was no association between ATP-III diagnostic criteria and endothelium-independent CMF. Similarly, there was no correlation between other continuous variables (age, LDL-cholesterol, CRP and adipocytokines) and endothelium-dependent/-independent CMF. On multivariate regression analysis the presence/absence of MS (β  =  −0.40; p = 0.04) was the only independent determinant of endothelium-dependent CMF (other covariates: age, gender, smoking, LDL-cholesterol, CRP, leptin, adiponectin, resistin). MS and the other covariates used in the multivariate analysis did not independently influence endothelium-independent CMF (β for MS −0.12; p = 0.36). Conclusion: In patients with stable coronary artery disease and optimal LDL levels, MS was an independent determinant of endothelium-dependent CMF. MS had no influence on endothelium-independent CMF.